Public acceptance of the government wallet application and implications for Thailand’s economic sustainability (International Journal of Management and Sustainability, 2026)
Along Thailand's post-pandemic journey through digital public finance, the Government Wallet Application (GWA) has become an important tool for delivering state aid and extending financial inclusivity. This research examines demographic, opinion, and behavior variables that shape public confidence in the GWA as it operates within the ERP. A total of 1,286 respondents were recruited via an online structured questionnaire, and a quantitative method was used. Binary logistic regression was utilized for the analysis. Results indicate that age, income, login frequency, anticipation of future FinTech, confidence in financial law, and E-Money trends significantly affect users' confidence in the platform (p < .05). Crucially, as the number of login attempts increases, confidence decreases, indicative of usability or authentication problems. While gender, student status, education level, LINE usage, and GWA usage do not have a significant impact at all. Trust in financial regulation is the most important driver, followed by perceptual factors. The research contributes to the literature on digital fiscal governance by demonstrating how government-run platforms contribute to increased economic resilience with more transparent and better-specified resource allocation, in support of SDG 8, SDG 9, and SDG 10. Results underscore that sustained uptake is dependent on the availability of digital infrastructure, the legitimacy of regulatory structures, and trust in institutions to deliver inclusive digitization.